2019
DOI: 10.1038/s41573-019-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for pharmacological targeting of pseudokinases

Abstract: Pseudokinases are members of the protein kinase superfamily but signal primarily through noncatalytic mechanisms. Many pseudokinases contribute to the pathologies of human diseases, yet they remain largely unexplored as drug targets owing to challenges associated with modulation of their biological functions. Our understanding of the structure and physiological roles of pseudokinases has improved substantially over the past decade, revealing intriguing similarities between pseudokinases and their catalytically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(139 citation statements)
references
References 290 publications
(312 reference statements)
2
128
0
9
Order By: Relevance
“…More broadly among pseudoenzymes, such functions likely speak to a noncatalytic substrate binding to an ancestral enzyme, which has evolved to perform a catalytic function, as has been demonstrated during in vitro evolution experiments (48,49) and by using structural features to evolve canonical activity in the pseudokinase CASK (Ca 2+ /calmodulin-activated serine/threonine kinase), where four amino acid substitutions are required to regenerate an Mg-ATPdependent enzyme (50). In a similar vein, improving the curation of (nonkinase) pseudoenzyme families will provide the scientific community with valuable information to understand the evolution of these proteins, the etiology of related diseases, and the development and repurposing of pseudoenzyme-targeted drugs, a useful bonus in carefully conducted pseudoenzyme studies (7,51,52).…”
Section: Structural Biology As a Key Driver In The Pseudokinase And Pmentioning
confidence: 99%
See 2 more Smart Citations
“…More broadly among pseudoenzymes, such functions likely speak to a noncatalytic substrate binding to an ancestral enzyme, which has evolved to perform a catalytic function, as has been demonstrated during in vitro evolution experiments (48,49) and by using structural features to evolve canonical activity in the pseudokinase CASK (Ca 2+ /calmodulin-activated serine/threonine kinase), where four amino acid substitutions are required to regenerate an Mg-ATPdependent enzyme (50). In a similar vein, improving the curation of (nonkinase) pseudoenzyme families will provide the scientific community with valuable information to understand the evolution of these proteins, the etiology of related diseases, and the development and repurposing of pseudoenzyme-targeted drugs, a useful bonus in carefully conducted pseudoenzyme studies (7,51,52).…”
Section: Structural Biology As a Key Driver In The Pseudokinase And Pmentioning
confidence: 99%
“…Formally, we propose that pseudoenzymes be defined as "the predicted catalytically defective counterparts of enzymes owing to an absence of one or more catalytic residue". It should come as no surprise that, in some cases, in which this simple description is applied, residual catalytic activities have been reported among proteins defined as pseudoenzymes (mainly pseudokinases), including the isolated pseudokinase domains for human epidermal growth factor receptor 3 (HER3, also known as EGFR3 or ERBB3), Janus kinase 2 [JAK2; pseudokinase domain called JAK homology-2 (JH2)], CASK, and Tribbles 2 (TRIB2) (7,50,64,65). However, because these very modest catalytic activities are either dispensable for biological function or not conserved in vitro among paralogous proteins across species (such as HER3/EGFR3[2) (24), this vestigial (or residual) catalytic activity is probably not a defining feature of their biological function.…”
Section: The Future Of Pseudoenzyme Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we show basal KinCon conformations with kinases from the mTOR pathway, some CDKs, and with kinases upstream of AMPK. It should be noted that the KinCon reporter principle may also provide functional insights into pseudokinase conformation dynamics . Recently, it has been demonstrated that nucleotide binding, substrate interactions, or small molecule interactions alter non‐catalytic protein‐interaction modules of pseudokinase .…”
Section: Tracking Kincon Activity Dynamicsmentioning
confidence: 99%
“…Proteins whose functionality is not well characterized form a large percentage of entries in many of the currently available biological databases, including the Protein Data Bank (PDB), and there is a constantly growing demand for reliable and fast synthesis and characterization methods. When it comes to drug discovery, proteins are key components as they can have therapeutic potential themselves (e.g., antibodies, coagulation factors, hormones, growth factors, enzymes, and antimicrobial peptides), but also because they could serve as drug targets for diverse diseases (as ion channels, receptors, enzymes, and transporters, for example) [1][2][3][4][5][6][7]. A large proportion of approved pharmaceutical drugs target human proteins.…”
Section: Introductionmentioning
confidence: 99%